Calibration of handphone camera of different resolutions using close range photogrammetry technique - 390979 Liew Heng Hai; Usmuni Din, supervisor; Fakulti Kejuruteraan dan Sains Geoinformasi (2010)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2010